IMPLEMENTASI EDUKASI NILAI-NILAI ETIKA DAN MORAL PADA SISWA DI SD NEGERI 107/VIII GIRI PURNO - Wiwik Dyah Aryani; Saeroji; Padriyah KrisnaWardani; Khodijah Rodiah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Ethics and moral education plays an essential role in shaping students' character from an early age. However, technological advancements, changes in the social environment, and the limited awareness of some students in practicing discipline, responsibility, honesty, and politeness have become challenges in the implementation of character education in schools. This study aimed to describe the implementation of ethics and moral values education among students at SD Negeri 107/VIII Giri Purno. The study employed a qualitative approach using a descriptive research design. The research participants consisted of the principal, classroom teachers, Islamic Religious Education teachers, students, and parents selected through purposive sampling. Data were collected through observation, interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña interactive model, which includes data condensation, data display, and conclusion drawing. The trustworthiness of the data was ensured through source triangulation, technique triangulation, and member checking. The findings revealed that the implementation of ethics and moral values education was carried out through integration into classroom learning, school habituation programs, teachers' role modeling, religious activities, and collaboration between the school and parents. The values emphasized included honesty, discipline, responsibility, politeness, caring, tolerance, and cooperation. Although several challenges were identified, such as environmental influences, students' diverse characteristics, and the uncontrolled use of digital media, the school's habituation and character-building programs contributed positively to developing students into ethical, moral, and responsible individuals in their daily lives.